KEMANDIRIAN DAN MOTIVASI BELAJAR MATEMATIKA DALAM PEMBELAJARAN DARING MATA KULIAH METODE NUMERIK: K-MEANS CLUSTER ANALYSIS - Nurcahyo, Adi; Setyowati, Elis; Rahma, Tara Kamila; Musthofa, Akbar Fadel Dwiki; Sudibyo, Nugroho Arif (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
The purpose of this study is to determine the clustering of student independence and learning motivation in the Numerical Methods course during online lectures. Based on the clustering carried out, clusters are obtained according to predetermined criteria. This can be a reference for educators to determine strategies to solve problems. The method used is cluster analysis with the K-Means method using Orange software. The research was carried out on 5th semester students who took Numerical methods courses for the 2020/2021 academic year as many as 4 classes. The data collection technique uses documentation methods derived from UTS scores in the Numerical Methods course for the 2020/2021 academic year and the questionnaire method for independence and motivation for online learning during the pandemic. The results obtained from the research conducted are that in cluster C1 students with independence and high motivation have high GPA and IPS as well. Meanwhile, the C2 cluster is dominated by students with a moderate level of independence and motivation who also have a medium IPS and GPA. In Cluster C3, students have a relatively moderate level of independence and motivation which results in low social studies and GPA. From these results, it can be concluded that the high and low social studies and GPA can be influenced by student independence and learning motivation.